THE ROLE OF LEADERSHIP AND WORK MOTIVATION IN IMPROVING EMPLOYEE PERFORMANCE: WITH JOB SATISFACTION INTERVENING VARIABLES - Qomariah, Nurul; Lusiyati, Lusiyati; Martini, Ni Nyoman Putu; Nursaid, Nursaid (Universitas Brawijaya, Indonesia, 2022)
This paper aims to examine the role of leadership style and work motivation in improving performance by involving feelings of satisfaction from employees (job satisfaction) as an intermediary variable in Freelance Daily Workers (THL) at the Banyuwangi Regional Secretary. The number of freelance daily workers (THL) at the Banyuwangi Regency Secretariat. The population in this study were all employees of the Daily Leasing Office of the Regional Secretariat of Banyuwangi Regency, amounting to 101 employees. Determination of the sample using a saturated sample so that the number of samples is 101 respondents. The descriptive analysis method is used to describe the respondents, and the variables used. Smart PLS 3.0 application is used in this study as an analytical tool to answer the hypothesis. The results showed that the leadership style variable in an organization could increase the job satisfaction of THL employees at the Banyuwangi Regional Secretariat. Work motivation from employees has a significant effect on job satisfaction. Job satisfaction of casual daily workers also affects employee performance. The leadership style possessed by the leaders at the Banyuwangi Regency Secretary also affects employee performance. Work motivation significantly affects employee performance at the Daily Leasing Office of the Regional Secretariat of Banyuwangi Regency. Leadership style and work motivation can increase employee satisfaction and performance at the Regional Secretary of Banyuwangi Regency. Therefore there needs to be an effort to improve employees' leadership style and work motivation.